The Role of the Income Statement (Profit and Loss) in Ngos - Kowalczyk, Magdalena (Studia Oeconomica Posnaniensia, 2015)
Non-governmental organizations as commercial entities practice accounting which is an integral part of financial reporting. The role of financial statements is to provide information about assets and sources of funding and the achievements of the organization during the year. Basic information about the size of the revenue generated and the incurred costs incurred by non-governmental organizations providing such income statements. This article attempts to present proposals for changes in the income statement for nongovernmental organizations that do not engage in economic activity and the profit and loss account prepared by the organizations conducting economic activity.